Hubungan Beban Kerja, Lingkungan Kerja dan Shift Kerja terhadap Stres Kerja Karyawan di PT. Generasi Muda Bersatu Kecamatan Simpenan, Kabupaten Sukabumi Tahun 2023 - Putra, Fathir Brahmastha Arya; Yaser, Mohamad; Saputra, Fajar (Journal of Public Health Education, 2024)
Introduction: Work stress is pressure experienced by everyone in living their work life, stress itself has two meanings namely positive and negative depending on how a person can deal with stress, in a positive view psychologically it will foster motivation and morale while in a negative sense it can reduce the level of employee performance. Objectives: The purpose of this study is to determine the relationship between workload, work environment and work shifts on employee work stress at PT. United Young Generation Simpenan District, Sukabumi Regency in 2023. Method: This research uses a quantitative research type with a cross-sectional design totaling 113 respondents to employees who work at PT. United Young Generation (GMB). The sampling technique is Random Sampling. The data used are primary data through questionnaires and observations and secondary data derived from books and literature. Data analysis was performed univariately and bivariately with the Chi-Square Test. Results: The research results show a relationship between work shifts (p-value = 0.000), and workload (p-value = 0.000). Work environment (p-value 0.496) with work stress. Conclusion: There is a relationship between work shifts, workload and work stress. However, there is no relationship between the work environment and work stress.